Low-glue self-compacting concrete mixing material and preparation method thereof

By using specific proportions of nano silica, zeolite and other materials in self-contained concrete mixing materials, the amount of cement and fly ash is reduced, and the problem of high content of cementitious materials in the prior art is solved, thus achieving the problem of poor durability due to high content of cementitious materials, and achieving Higher durability and stability while maintaining good construction performance.

CN119461965APending Publication Date: 2025-02-18PUNING JIRUN CONCRETE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411593821.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When the existing self-finished concrete mixtures improve fluidity, the gelling material content is high, resulting in poor durability of concrete.

Method used

By using specific proportions of nanosilicon dioxide, zeolite, limestone, carboxymethylcellulose and reinforced fibers, the amount of cement and fly ash is reduced while maintaining the flowability of the concrete mixture.

Benefits of technology

It effectively reduces the content of cementitious materials in concrete, improves the durability and stability of concrete, and maintains good construction performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005126256580000071
    Figure BDA0005126256580000071
Patent Text Reader

Abstract

The invention relates to the field of concrete, and particularly discloses a low-glue self-compacting concrete mixture and a preparation method thereof. The invention relates to a low-glue self-compacting concrete mixing material, which comprises the following components by mass: 190-200 parts of cement; 175 to 185 parts of water; 840 to 850 parts of sand; 890 to 900 parts of broken stone; 10 to 15 parts of a water reducing agent; 170 to 180 parts of fly ash; 30 to 40 parts of nano silicon dioxide; 5 to 10 parts of zeolite; 15 to 20 parts of limestone; 1 to 3 parts of carboxymethyl cellulose; and 14-21 parts of reinforcing fibers. The concrete mixture disclosed by the invention has the advantage of relatively low content of a cementing material. The preparation method of the low-glue self-compacting concrete mixture comprises the step of uniformly mixing the components to obtain the low-glue self-compacting concrete mixture. The preparation method also has the advantage of simple and convenient preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of concrete, in particular to a low-glue self-compacting concrete admixture and a preparation method thereof. Background Art

[0002] Since concrete shrinks during the hardening process, especially in the early hardening stage, this shrinkage may cause tiny cracks in the structure. Therefore, when designing concrete structures, gaps are usually reserved, such as expansion joints, settlement joints, etc., to better adapt to changes in the structure. However, the reserved gaps not only affect the appearance of the structure, but may also become a safety hazard, providing space for water accumulation, breeding of bacteria, insects and animals, etc. Therefore, after the construction is completed, it is usually necessary to use concrete mixture to fill the reserved gaps.

[0003] Since self-compacting concrete mixture has high fluidity and can flow freely without vibration during the pouring process, it can better fill the gaps in the formwork and the gaps between the steel bars. Therefore, self-compacting concrete mixture is generally used as the material for filling the gaps.

[0004] However, in order to meet the high fluidity performance of self-compacting concrete mixtures, self-compacting concrete mixtures are usually required to contain a higher content of cementitious materials, which easily leads to poor durability of the concrete formed by solidification. Therefore, there is still room for improvement. Summary of the invention

[0005] In order to reduce the content of cementitious materials in concrete while ensuring the fluidity of the self-compacting concrete mixture, thereby taking into account the durability of the concrete, the present application provides a low-cement self-compacting concrete mixture and a preparation method thereof.

[0006] In the first aspect, the present application provides a low-glue self-compacting concrete mixture, which adopts the following technical solution: A low-glue self-compacting concrete mixture, comprising the following components in parts by weight: 190-200 parts of cement; 175-185 parts of water; Sand 840-850 parts; 890-900 parts of crushed stone; 10-15 parts of water reducing agent; 170-180 parts of fly ash; 30-40 parts of nano silicon dioxide; Zeolite 5-10 parts; 15-20 parts of limestone; 1-3 parts of carboxymethyl cellulose; 14-21 parts of reinforcing fiber.

[0007] By adopting the above technical scheme, nano-silicon dioxide, zeolite, limestone, carboxymethyl cellulose and reinforcing fibers cooperate with each other in a specific proportion, which is conducive to reducing the amount of cement and fly ash in the concrete mixture, thereby helping to reduce carbon dioxide emissions and other harmful substances in the production process, and more in line with the requirements of green environmental protection; at the same time, the above fillers are also conducive to significantly improving the microstructure of the concrete formed after the low-glue self-compacting concrete mixture solidifies, reducing the porosity, thereby better improving the stability and durability of the concrete; in addition, while it is conducive to accelerating the hydration reaction of cement, shortening the setting time and improving the early strength, it is also conducive to better maintaining the moisture and temperature of the concrete mixture during the setting process, and making the release of hydration heat more uniform, so that the concrete after solidification is less likely to crack due to temperature stress concentration, which is conducive to further improving the stability and durability of the concrete; the compounding of the dosage ratios of the above-mentioned substances is also conducive to maintaining the fluidity of the overall system of the concrete mixture, so that the construction performance of the low-glue self-compacting concrete is better.

[0008] Preferably, the water reducing agent is one or more of sodium lignin sulfonate, calcium lignin sulfonate, magnesium lignin sulfonate, potassium lignin sulfonate, sodium xylonate, calcium xylonate, sodium sulfite, calcium sulfite, tannic acid, molasses, and calcium sugar.

[0009] By selecting the above-mentioned specific water reducer, it is helpful to reduce the water consumption, thereby reducing the hydration heat of the concrete mixture during the solidification process, making the concrete less likely to crack after solidification, which is helpful to better improve the stability and durability of the concrete.

[0010] Preferably, the water reducing agent is a mixture of sodium lignin sulfonate, calcium sulfite, tannic acid and calcium sugar in a mass ratio of (3-5):(0.5-0.7):(0.5-0.8):(1-1.5).

[0011] By selecting a specific proportion of sodium xylonate, calcium sulfite, tannic acid and sugar calcium as a synergistic compound as a water reducer, it is beneficial to further improve the fluidity of the low-glue self-compacting concrete mixture, thereby improving the construction performance of the low-glue self-compacting concrete mixture; at the same time, it also makes the hydration heat released by the concrete mixture during the setting process more uniform, making the concrete after setting less likely to crack due to temperature stress concentration, which is beneficial to further improve the stability and durability of the concrete.

[0012] Preferably, the reinforcing fiber is a compound of dura fiber and glass fiber.

[0013] By selecting a combination of dura fiber and glass fiber as reinforcing fibers, the reinforcing fibers can be better compounded with other fillers, thereby helping to better improve the microstructure of the concrete after the concrete mixture solidifies, thereby improving the stability and durability of the concrete.

[0014] Preferably, the mass ratio of the Dura fiber to the glass fiber is (12-15):(2-6).

[0015] By using a specific ratio of Dura fiber and glass fiber as reinforcing fibers, the reinforcing fibers can better cooperate with other fillers to improve the microstructure of concrete, thereby improving the stability and durability of concrete. At the same time, it is not easy to affect the fluidity of the concrete mixture.

[0016] Preferably, the particle size range of the crushed stone is 5-15 mm, and the fineness modulus of the sand is 2.7.

[0017] By controlling the particle size range of crushed stone and sand, various fillers in the low-glue self-compacting concrete mixture can be better coordinated and compounded, thereby more significantly improving the microstructure of the concrete, making the concrete condensed from the low-glue self-compacting concrete mixture have higher density, better stability and durability.

[0018] Preferably, the fly ash is Class II fly ash.

[0019] By selecting Class II fly ash, the activity of fly ash is made higher, which is conducive to further reducing the amount of cement used.

[0020] In a second aspect, the present application provides a method for preparing a low-glue self-compacting concrete mixture, using the following technical solution: A method for preparing a low-glue self-compacting concrete mixture comprises the following steps: Step 1, first mix cement, sand and gravel and stir evenly, then add water and stir evenly to obtain a premix; Step 2, add zeolite, limestone, reinforcing fiber and water reducing agent, stir evenly, then add fly ash, nano silicon dioxide and carboxymethyl cellulose in sequence while stirring, stir evenly, and obtain low-glue self-compacting concrete mixture.

[0021] By stirring and mixing the materials in a specific order, it is beneficial to better and more evenly stir the components, thereby facilitating better coordination between the components, making the low-glue self-compacting concrete mixture have better fluidity. At the same time, while helping to accelerate the coagulation of the low-glue self-compacting concrete mixture, it is also beneficial to better regulate the hydration heat released by the concrete mixture during the coagulation process, thereby shortening the coagulation time of the low-glue self-compacting concrete mixture, making the coagulated concrete less likely to crack, and further improving the stability and durability of the concrete.

[0022] In summary, this application has the following beneficial effects: 1. By adopting a specific proportion of water, cement, sand, stone, water reducing agent, filler and other ingredients for synergistic compounding, it is beneficial to better reduce the amount of cement and fly ash, while also helping to better maintain the fluidity of the overall system of low-glue self-compacting concrete mixture, so that the construction performance is better; at the same time, it is also beneficial to better improve the microstructure of concrete, so that the concrete formed by condensation can achieve higher density and better durability without affecting the fluidity of the mixture.

[0023] 2. By stirring and mixing the materials in a specific order, it is beneficial to fully and evenly stir the components, which is beneficial to better coordinate the components and make the fluidity of the low-glue self-compacting concrete mixture better. At the same time, it is also beneficial to better improve the internal microstructure of the concrete, and further improve the stability and durability of the concrete without affecting the fluidity of the concrete mixture. DETAILED DESCRIPTION

[0024] The present application is further described in detail below in conjunction with embodiments.

[0025] The materials in the following examples and comparative examples are all commercially available, as follows: Cement was purchased from Fujian Tapai Cement Co., Ltd. as PO42.5 cement; Sand was purchased from Puning Jierun Concrete Co., Ltd., artificial sand, with a fineness modulus of 2.7; The crushed stone was purchased from Hukeng Stone Quarry in Nankou Town, Meixian District, Meizhou City, and the particle size range of the crushed stone was 5-15 mm; The fly ash was purchased from Class F II fly ash of Jieyang Huilai Power Plant; Sodium lignin sulfonate was purchased from Shandong Hongquan Chemical Technology Co., Ltd., CAS No. 8061-51-6; Calcium sulfite was purchased from Lingshou County Tianze Mineral Products Processing Plant with a particle size of 4 μm; Tannic acid was purchased from Tesco Chemical (Hubei) Co., Ltd., CAS No. 1401-55-4; Sugar calcium was purchased from Shandong Zengfu Industry and Trade Co., Ltd., product number 20201031; Nano-silicon dioxide was purchased from Xuancheng Jingrui New Materials Co., Ltd., model VK-SH30; Zeolite was purchased from Wuhu Honghuashan Zeolite Mining Co., Ltd., with a particle size of 1.0-2.0 mm; Limestone was purchased from Jintong Lime Powder Manufacturing Plant in Shilin County, with a mesh size of 600; Carboxymethyl cellulose was purchased from Dacheng County Yibo Chemical Co., Ltd., product number 4132; Dura fiber was purchased from Laiwu Jingkai Engineering Materials Co., Ltd., with a fiber length of 6 mm; Glass fiber was purchased from Hebei Houkang Mineral Products Co., Ltd., with a fiber length of 3-19 mm and a fiber diameter of 9-13 μm; Nanocarbon fiber powder was purchased from Qinghe County Ruijiang Metal Materials Co., Ltd., with a particle size of 100-200 nm; Ceramic granules were purchased from Qingdao Bohong Environmental Technology Co., Ltd.; Talc powder was purchased from Lingshou County Yongkuang Products Co., Ltd., with a mesh size of 600; Hydroxypropyl methylcellulose was purchased from Shandong Shenmao Chemical Co., Ltd., CAS No. 9004-65-3; Steel fiber was purchased from Hengshui Haichen New Material Technology Co., Ltd., with a size of 38*6mm; Carbon fiber was purchased from Jiangxi Shuobang New Material Technology Co., Ltd., model 3MM; Calcium lignin sulfonate was purchased from Jinan Qinghai Chemical Co., Ltd.; Sodium sulfite was purchased from Chengdu Dinghengda Chemical Products Co., Ltd.; Molasses was purchased from Jinan Qianqi Chemical Co., Ltd.

[0026] Example 1 The present application embodiment discloses a low-glue self-compacting concrete mixture, which is composed of the following components: 190kg cement; 175kg water; 840kg sand; 890kg crushed stone; 10kg water reducer; 170kg fly ash; 30kg nano-silicon dioxide; 5kg zeolite; 15kg limestone; 1kg carboxymethyl cellulose; 14kg reinforcing fiber.

[0027] In this embodiment, the water reducer is a mixture of sodium lignin sulfonate, calcium sulfite, tannic acid and calcium sugar in a mass ratio of 3:0.5:0.5:1, that is, the water reducer is a mixture of 6 kg of sodium lignin sulfonate, 1 kg of calcium sulfite, 1 kg of tannin and 2 kg of calcium sugar.

[0028] The reinforcing fiber is a mixture of Dura fiber and glass fiber in a mass ratio of 12:2, that is, the reinforcing fiber is a mixture of 12 kg of Dura fiber and 2 kg of glass fiber.

[0029] The present application also discloses a method for preparing a low-glue self-compacting concrete mixture, comprising the following steps: Step 1, weigh the materials according to the above mass, and put cement, sand and gravel into a stirring kettle, stir at a speed of 60r / min for 10min, then add water, and continue stirring for 20min to obtain a premix.

[0030] Step 2, continue to add zeolite, limestone, dura fiber, glass fiber, sodium lignin sulfonate, calcium sulfite, tannic acid and calcium sugar to the premix, continue stirring at a speed of 60r / min for 15 minutes, after stirring evenly, add fly ash, nano-silicon dioxide and carboxymethyl cellulose in sequence while stirring, and continue stirring for 20 minutes to obtain a low-glue self-compacting concrete mixture.

[0031] Example 2 The difference from Example 1 is that the addition amount of each substance is different, as follows: 200kg cement; 185kg water; 850kg sand; 900kg crushed stone; 15kg water reducer; 180kg fly ash; 40kg nano-silicon dioxide; 10kg zeolite; 20kg limestone; 3kg carboxymethyl cellulose; 21kg reinforcing fiber.

[0032] In this embodiment, the water reducer is a mixture of sodium lignin sulfonate, calcium sulfite, tannic acid and calcium sugar in a mass ratio of 5:0.7:0.8:1.5, that is, the water reducer is a mixture of 9.375 kg of sodium lignin sulfonate, 1.3125 kg of calcium sulfite, 1.5 kg of tannic acid and 2.8125 kg of calcium sugar.

[0033] The reinforcing fiber is a mixture of Dura fiber and glass fiber in a mass ratio of 15:6, that is, the reinforcing fiber is a mixture of 15 kg of Dura fiber and 6 kg of glass fiber.

[0034] Example 3 The difference from Example 1 is that the addition amount of each substance is different, as follows: 195kg cement; 180kg water; 845kg sand; 895kg crushed stone; 12kg water reducer; 175g fly ash; 35kg nano-silicon dioxide; 8kg zeolite; 17kg limestone; 2kg carboxymethyl cellulose; 18kg reinforcing fiber.

[0035] In this embodiment, the water reducer is a mixture of sodium lignin sulfonate, calcium sulfite, tannic acid and calcium sugar in a mass ratio of 3.5:0.6:0.7:1.2, that is, the water reducer is a mixture of 7 kg of sodium lignin sulfonate, 1.2 kg of calcium sulfite, 1.4 kg of tannic acid and 2.4 kg of calcium sugar.

[0036] The reinforcing fiber is a mixture of Dura fiber and glass fiber in a mass ratio of 14:4, that is, the reinforcing fiber is a mixture of 14 kg of Dura fiber and 4 kg of glass fiber.

[0037] Comparative Example 1 The difference from Example 3 is that an equal amount of nano-carbon fiber powder is used to replace nano-silicon dioxide.

[0038] Comparative Example 2 The difference from Example 3 is that the zeolite is replaced by an equal amount of ceramsite.

[0039] Comparative Example 3 The difference from Example 3 is that the limestone is replaced by an equal amount of talcum powder.

[0040] Comparative Example 4 The difference from Example 3 is that an equal amount of hydroxypropyl methylcellulose is used to replace carboxymethyl cellulose.

[0041] Comparative Example 5 The difference from Example 3 is that an equal amount of steel fibers are used to replace the Dura fibers.

[0042] Comparative Example 6 The difference from Example 3 is that an equal amount of carbon fiber is used to replace the glass fiber.

[0043] Comparative Example 7 The difference from Example 3 is that the water reducer is a mixture of calcium lignin sulfonate, sodium sulfite, tannic acid and molasses in a mass ratio of 3.5:0.6:0.7:1.2, that is, the water reducer is a mixture of 7 kg of calcium lignin sulfonate, 1.2 kg of sodium sulfite, 1.4 kg of tannic acid and 2.4 kg of molasses.

[0044] Comparative Example 8 The difference from Example 3 is that an equal amount of nano-carbon fiber powder is used to replace nano-silicon dioxide; an equal amount of ceramsite is used to replace zeolite; an equal amount of talc is used to replace limestone; an equal amount of hydroxypropyl methylcellulose is used to replace carboxymethyl cellulose; an equal amount of steel fiber is used to replace dura fiber; an equal amount of carbon fiber is used to replace glass fiber; the water reducer is a mixture of calcium lignin sulfonate, sodium sulfite, tannic acid and molasses in a mass ratio of 3.5:0.6:0.7:1.2, that is, the water reducer is a mixture of 7kg of calcium lignin sulfonate, 1.2kg of sodium sulfite, 1.4kg of tannic acid and 2.4kg of molasses.

[0045] Comparative Example 9 The difference from Comparative Example 8 is that the amount of cement added is 250 kg; the amount of fly ash added is 200 kg; and the amount of water added is 200 kg.

[0046] Experiment 1 According to the 4.1 slump test in GB / T 50080-2016 "Standard for Performance Test Methods of Ordinary Concrete Mixtures", the slump (mm) of the concrete mixtures prepared in the above examples and comparative examples were respectively tested, and according to the 5.1 spread test therein, the spread (mm) of the concrete mixtures prepared in the above examples and comparative examples were respectively tested.

[0047] Experiment 2 The low-glue self-compacting concrete mixtures prepared in the above embodiments and comparative examples were respectively cast into molds and cured at 22°C for 28 days to make prismatic specimens with a size of 100 mm×100 mm×300 mm. The compressive fatigue deformation values ​​(mm / m) of the prismatic specimens prepared above were tested according to the 13 compressive fatigue deformation test in GB / T50082-2009 "Standard for Test Methods for Long-term Properties and Durability of Ordinary Concrete".

[0048] Experiment 3 The low-glue self-compacting concrete mixtures prepared in the above embodiments and comparative examples were respectively cast into molds and cured at 22°C for 28 days to make cubic specimens with a size of 100 mm×100 mm×100 mm. The sulfate resistance level of the cubic specimens prepared above was tested according to the 14 sulfate resistance test in GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete".

[0049] The test data of the above experiments are detailed in Table 1.

[0050] Table 1 According to the data comparison between Example 3 and Comparative Examples 1-7 in Table 1, it can be obtained that no matter which component of nano-silica, zeolite, limestone, carboxymethyl cellulose, dura fiber, glass fiber, and water reducer is replaced in Comparative Examples 1-7, it is difficult to improve the durability of the concrete formed by the coagulation of the low-glue self-compacting concrete. Even if the durability of Comparative Example 7 reaches a relatively good level, the slump and expansion of Comparative Example 7 are greatly reduced, which is difficult to meet the construction requirements. That is, only by using nano-silica, zeolite, limestone, carboxymethyl cellulose, dura fiber, glass fiber and water reducer in a coordinated manner can the durability of the concrete be improved without affecting the fluidity of the low-glue self-compacting concrete mixture.

[0051] According to the data comparison between Example 3 and Comparative Examples 8-9 in Table 1, it can be obtained that Comparative Example 8 replaces other conventional fillers and water reducing agents, and it is difficult to achieve the effects of fluidity and self-compacting when the content of cementitious materials is low. Comparative Example 9 increases the amount of cementitious materials on the basis of Comparative Example 8. Although Comparative Example 9 achieves the effects of fluidity and self-compacting, the durability is also greatly affected. That is, only by using nano-silica, zeolite, limestone, carboxymethyl cellulose, dura fiber, glass fiber and water reducing agent in a coordinated manner can the fluidity of the concrete mixture and the durability of the concrete be guaranteed under the premise of low glue.

[0052] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A low-glue self-compacting concrete mixture, characterized by: The composition includes the following components in parts by weight: 190-200 parts of cement; 175-185 parts of water; Sand 840-850 parts; 890-900 parts of crushed stone; 10-15 parts of water reducing agent; 170-180 parts of fly ash; 30-40 parts of nano silicon dioxide; Zeolite 5-10 parts; 15-20 parts of limestone; 1-3 parts of carboxymethyl cellulose; Reinforcing fiber 14-21 parts.

2. A low-glue self-compacting concrete mixture according to claim 1, characterized in that: The water reducing agent is one or more of sodium lignin sulfonate, calcium lignin sulfonate, magnesium lignin sulfonate, potassium lignin sulfonate, sodium xylonate, calcium xylonate, sodium sulfite, calcium sulfite, tannic acid, molasses, and calcium sugar.

3. A low-glue self-compacting concrete mixture according to claim 2, characterized in that: The water reducing agent is prepared by mixing sodium lignin sulfonate, calcium sulfite, tannic acid and calcium sugar in a mass ratio of (3-5): (0.5-0.7): (0.5-0.8): (1-1.5).

4. A low-glue self-compacting concrete mixture according to any one of claims 1 to 3, characterized in that: The reinforcing fiber is a compound of dura fiber and glass fiber.

5. A low-glue self-compacting concrete mixture according to claim 4, characterized in that: The mass ratio of the Dura fiber to the glass fiber is (12-15):(2-6).

6. A low-glue self-compacting concrete mixture according to any one of claims 1 to 3, characterized in that: The particle size of the crushed stone ranges from 5 to 15 mm, and the fineness modulus of the sand is 2.

7.

7. A low-glue self-compacting concrete mixture according to any one of claims 1 to 3, characterized in that: The fly ash is Class II fly ash.

8. A method for preparing a low-glue self-compacting concrete mixture according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1, first mix cement, sand and gravel and stir evenly, then add water and stir evenly to obtain a premix; Step 2, add zeolite, limestone, reinforcing fiber and water reducing agent, stir evenly, then add fly ash, nano silicon dioxide and carboxymethyl cellulose in sequence while stirring, stir evenly, and obtain low-glue self-compacting concrete mixture.